Successful outcome of a giant inguinoscrotal hernia: a novel two-staged repair using preoperative progressive pneumoperitoneum and transversus abdominis release. Issue 12 (17th December 2020) - Miller, Derek B; Reed, Logan
Abstract: Giant inguinoscrotal hernias, defined as the extension beyond the midpoint of the inner thigh, continue to require multi-step approaches due to their complexity. Although rare in developed countries, they are commonly present in rural areas after years of neglect. This consequently allows the abdomen to maladapt to lower volumes, creating a loss of domain. Here, we present a giant left inguinoscrotal hernia managed with a unique multi-stage approach, aimed to minimize commonly encountered perioperative complications associated with abdominal hypertension. The combined two-staged approach used begins with preoperative progressive pneumoperitoneum, followed by the combined procedures of laparotomy hernia repair (Stoppa technique) and transversus abdominis release, thereby promoting a tension-free closure that is able to accommodate the reduced contents. Various modalities used in treating these hernias have been previously described; however, to our knowledge, the combined use of techniques described here has not been reported.